Inner Form of Word as Phenomenon of Ordinary Metalinguistic Consciousness - A. I. Olkhovskaya (Научный диалог, 2017)
The article is devoted to the inner form of the word as a living mechanism of ordinary metalinguistic consciousness. Three types of inner forms are distinguished - trivial, lost and darkened, the author focuses on the last one, as it represents the greatest interest within the framework of naive linguistics. To identify the principles of its functioning in consciousness of native speakers the author refers to the experiment and processing of the results obtained by four parameters: (1) correctness, (2) consistency, (3) strategy for establishing the inner form of the word, and (4) the type of error in its interpretation. The survey allowed to draw a number of conclusions. First of all, it is established that darkened inner form is virtually not recognized by native speakers and therefore cannot be considered a living element of the meaning of the word. Secondly, it is revealed that the interpretation of the inner form, even in the case of an erroneous result rarely goes beyond the capabilities of the language system. Thirdly, it is determined that among the strategies for establishing the inner form of the word the analysis of its root while ignoring the other components of morphemic structure assumes the leading position. Fourthly, it is found that the most frequent error in interpretation of the inner form is incorrect commenting the image, that forms the basis of the nomination.